Venture capital contracting as bargaining in the shadow of corporate law constraints - Luca Enriques; Casimiro A. Nigro; Tobias Tröger (Goethe University, Center for Advanced Studies on the Foundations of Law and Finance (LawFin), 2025)
Venture capital ("VC") has built a solid reputation for spurring innovation and economic growth, thus emerging as a crown jewel of the U.S. economy since the 1980s. The development of the U.S. VC market has benefited from the enabling nature of U.S. (Delaware) corporate law, which allows parties to devise a complex contractual framework that economists consider the best realworld solution to the market frictions bedeviling the finance of high-tech innovative projects. The law and finance literature has paid attention to corporate law as one of the determinants of VC investments by examining how variations in shareholder protection shape VC contracting. It has underscored the importance of flexible corporate law to enable the tailor-made arrangements that define VC-backed firms' unique governance structure. Vice versa, it has also documented anecdotally how mandatory corporate laws can impede the adoption and use of some specific components of the U.S. contractual framework. This article contributes to this literature, first, by conceptualizing, in a general theoretical framework, the role that flexible or rigid corporate law in action plays in supporting or hindering VC. Second, it identifies the channels through which mandatory corporate law constrains VC contracting. Third, it documents the real-world significance of these phenomena by illustrating how the constraints stemming from the corporate law regimes in force in two European jurisdictions, namely Germany and Italy, impact the transplant of the contractual framework governing VC deals in the U.S.
Keywords: G38; K22; L26; 330; Comparative Corporate Law; Comparative Corporate Governance; Entrepreneurship; Financial Contracting; Private ordering; Start-ups; Venture Capital